2009
DOI: 10.1152/ajpgi.00555.2007
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of HO-1 and its generated products (CO, bilirubin, and Fe) in ethanol-induced human hepatocyte damage

Abstract: It has been reported that naturally occurring quercetin exerts hepatoprotective effects through heme oxygenase-1 (HO-1) induction. However, the precise mechanism of how ethanol-associated liver damage is counteracted by quercetin-enhanced HO-1 metabolism still remains unclear. To further decipher the protective role of quercetin on ethanol-induced liver damage, we treated human hepatocytes with quercetin and various (end) products of the HO-1 pathway. Our data clearly showed that quercetin treatment attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…42,43 Recent studies have shown that up-regulating HO-1 in Kupffer cells by means of overexpression or by pharmacological activators prevents alcohol-induced release of inflammatory mediators by Kupffer cells. 31,41 However, characterization of HO-1 inducers in Kupffer cells remains poorly documented. Our data identify HO-1 as a novel target of CB2 receptors, as shown both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Recent studies have shown that up-regulating HO-1 in Kupffer cells by means of overexpression or by pharmacological activators prevents alcohol-induced release of inflammatory mediators by Kupffer cells. 31,41 However, characterization of HO-1 inducers in Kupffer cells remains poorly documented. Our data identify HO-1 as a novel target of CB2 receptors, as shown both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the previous studies have used HO-1 inducers to up-regulate the expression of HO-1 in transplant recipients. The shortcoming of this method is obvious, as the entire body of the recipient becomes exposed to HO-1 after systemic administration of the inducer [4]. Further, the treatment requires substantial amounts of the inducer agent for an extended period after organ grafting.…”
Section: Discussionmentioning
confidence: 99%
“…It has attracted particular interest due to its extensive physiological functions, and potential therapeutic application [4]. A number of studies have demonstrated that HO-1 and its products display anti-inflammatory [5], anti-oxidative [6] and antiapoptotic [7,8] activities.…”
Section: Introductionmentioning
confidence: 99%
“…In another in vitro study, the protective effect of the flavonoid, quercetin, on the hepatotoxicity of ethanol was attributed to its induction of HO-1 in hepatocytes because the effects of quercetin were abrogated by treatment with zinc mesoporphyrin (Yao et al, 2009). Addition of free iron increased the damage caused by ethanol, whereas CO treatment protected the cells from ethanol-induced toxicity.…”
Section: In Vitro Evidence For the Cytoprotective Role Of Ho-1mentioning
confidence: 99%